2020
DOI: 10.13057/biodiv/d210453
|View full text |Cite
|
Sign up to set email alerts
|

Elevation influence the macrofungi diversity and composition of Gunung Korbu, Perak, Malaysia

Abstract: Abstract. Nur ‘Aqilah MB, NurJannah S, Salleh S, Thi BK, Ahmad Fitri Z, Mohd Khairul Faizi M, Haja Maideen KM, Nizam MS. 2020. Title. Biodiversitas 21: 1707-1713. Fructification of macrofungi depends on two main factors, abiotic and biotic. In this study, the main focus is to determine the macrofungi composition and diversity as the effect of elevation and substrate. Macrofungi collection was conducted at three different elevations along the trails (Trail A, B, and C) of Gunung Korbu in July 2019. The sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…For instance, the EMF genera Russula , Cortinarius and Laccaria was reported to harbor the most abundant species in Irish, British spruce and Scots pine forests (Orton, 1986; Alexander & Watling, 1987; Senn‐Irlet & Bieri, 1999; O'Hanlon et al 2013). The data derived from our plots within tropical forests indicate that the dominant macrofungal groups were all saprotrophic ( Marasmius , Mycena ), again confirming the results of previous research (Lopez‐Quintero et al 2012; Bakray et al 2020). Lopez‐Quintero et al (2012) found that saprobic fungi belonging to Polyporaceae, Marasmiaceae and Agaricaceae were the dominant fungal groups in all their study plots in the Amazon rain forest.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, the EMF genera Russula , Cortinarius and Laccaria was reported to harbor the most abundant species in Irish, British spruce and Scots pine forests (Orton, 1986; Alexander & Watling, 1987; Senn‐Irlet & Bieri, 1999; O'Hanlon et al 2013). The data derived from our plots within tropical forests indicate that the dominant macrofungal groups were all saprotrophic ( Marasmius , Mycena ), again confirming the results of previous research (Lopez‐Quintero et al 2012; Bakray et al 2020). Lopez‐Quintero et al (2012) found that saprobic fungi belonging to Polyporaceae, Marasmiaceae and Agaricaceae were the dominant fungal groups in all their study plots in the Amazon rain forest.…”
Section: Discussionsupporting
confidence: 91%
“…A key objective in studying the ecological processes behind macrofungal community formation is to better understand which factors shape the distribution patterns of macrofungal communities (Martiny et al 2006). Previous research has reported that both biotic and abiotic elements influence macrofungal diversity and distribution, including geographical, climatic, soil and floristic cover (O'Dell et al 2000; Gassibe et al 2015; Bakray et al 2020; Schimann et al 2020). Among these factors, plant community structures have been suggested to be more strikingly correlated with the diversity and structure of fungal communities (Peay et al 2013; Mueller et al 2014; Chen et al 2017; Bittebiere et al 2020; Francioli et al 2020; Pecoraro et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Community data, the abundance of each species found and species richness, were standardized by the rarefaction method (based on the smallest sample size) (Johnson and Bhattacharyya 2010). The diversity indices used were Shannon-Wiener index (H'), Gini-Simpson index (1-D), the effective number of species from H', community dominance index used Berger-Parker dominance, and Rényi entropy for relative measures of community diversity and evenness (Tóthmérész 1995;Jost 2006;Maurer and McGill 2010;Leinster and Cobbold 2012;Morris et al 2014;Mbenoun et al 2017;dos Santos et al 2020;Nur 'Aqilah et al 2020). Species accumulation curves were generated by collector and random methods with 1000 permutations (Schön et al 2018;Atrena et al 2020;Kärvemo et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2. The diversity index of a species is influenced by the presence of the number of individuals in a place (Bakray et al, 2020). There are 70 individuals in an area of 400 m2 or equal to 350 individuals/ha.…”
Section: Structure and Composition Of Macroscopic Fungi On The First ...mentioning
confidence: 99%